2019
DOI: 10.4239/wjd.v10.i4.260
|View full text |Cite
|
Sign up to set email alerts
|

Are serum leptin levels predicted by lipoproteins, vitamin D and body composition?

Abstract: BACKGROUND Both obesity and vitamin D deficiency are important health issues in Pakistan. The connection between body composition, Vitamin D and leptin in young adults is important to be studied as body composition may affect bone health and therefore the possibility of osteoporosis in later life. Few studies have attempted to investigate the effect of body composition and leptin with vitamin D in adolescence. AIM To investigate the association of serum leptin with body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…The dilemma is that unlike the west, Pakistan does not have a mandatory vitamin D fortification policy in place. Reports have shown that body composition, especially obesity, also increases the prevalence of VDD, and the prevalence of obesity in Pakistan is also reportedly higher ( 23 , 24 ). Anthropometry and body composition are the measurements of certain parameters of the human body and are frequently used to assess nutritional status as well as growth and development of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The dilemma is that unlike the west, Pakistan does not have a mandatory vitamin D fortification policy in place. Reports have shown that body composition, especially obesity, also increases the prevalence of VDD, and the prevalence of obesity in Pakistan is also reportedly higher ( 23 , 24 ). Anthropometry and body composition are the measurements of certain parameters of the human body and are frequently used to assess nutritional status as well as growth and development of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies did not mention demographic areas (urban/rural) for study population, 4 studies were conducted among urban populations and two studies included both rural and urban populations. Socio economic status for study participants was not mentioned in most of the studies, 8 studies were conducted on both lower and upper socio-economic groups of population and only one study was conducted on lower class population [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. The weighted mean level of vitamin D for study participants was 17.93ng/mL (weighted SD 8.24 ng/mL) [Mean vitamin D level ranged from 8.44 ng/mL to 32ng/mL] and random effect meta-analysis showed that the weighted pooled prevalence of vitamin D de ciency was 73% [95% CI: 63% to 83%] with high degree of heterogeneity (I 2 = 98.20%; p =0.00).…”
Section: Indiamentioning
confidence: 99%
“…The distribution of fat in adolescents with BMI of 36 ± 5 and %BF of 40 ± 5 might be associated with vitamin D status with decreased 25(OH)D (13). A recent study in young adults aged 20-21 years found that males and females demonstrated positive relationships between serum leptin and BMI, waist circumference, and %BF; however, males showed inverse correlations between serum leptin, MM, and 25(OH)D (5). In adults, the relationship between total body fat and 25(OH)D levels also varied by sex (14).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, serum leptin concentrations are higher in early adolescence than in childhood and may play a role in pubertal development (4). Body fat percentage (%BF), basal metabolic rate, muscle mass (MM), bone mass, and serum 25-hydroxyvitamin D (25(OH)D) had an impact on serum leptin (5).…”
Section: Introductionmentioning
confidence: 99%